2020
DOI: 10.1055/a-1331-7021
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dkk2 in the Muscle/bone Interaction of Androgen-Deficient Mice

Abstract: Androgen deficiency is known to cause both osteoporosis and sarcopenia. Myokines, humoral factors secreted from the skeletal muscles, have recently been getting attention as the key factors related to the interactions between muscle and bone. Dickkopf (Dkk) 2 is known as an inhibitor of canonical Wnt/β-catenin signaling, and Wnt/β-catenin signaling is crucial for the maintenance of muscle and bone. The present study was therefore performed to investigate the roles of Dkk2 in the alterations of muscle and bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This model helps researchers understand the role of androgens, such as testosterone, in the regulation of muscle and bone health and evaluate the efficacy of androgen replacement therapies. Iemura S ( 14 ) show that androgen deficiency increases the expression and secretion of Dickkopf (Dkk) 2, an inhibitor of Wnt/β-linker signaling, which is essential for maintaining muscle and bone function, in the muscles of mice. The research team initially demonstrated that Dkk2 plays a role in muscle and bone alterations in androgen-deficient mice.…”
Section: Resultsmentioning
confidence: 99%
“…This model helps researchers understand the role of androgens, such as testosterone, in the regulation of muscle and bone health and evaluate the efficacy of androgen replacement therapies. Iemura S ( 14 ) show that androgen deficiency increases the expression and secretion of Dickkopf (Dkk) 2, an inhibitor of Wnt/β-linker signaling, which is essential for maintaining muscle and bone function, in the muscles of mice. The research team initially demonstrated that Dkk2 plays a role in muscle and bone alterations in androgen-deficient mice.…”
Section: Resultsmentioning
confidence: 99%